(untitled) (KEMANUSIAAN The Asian Journal of Humanities, 2023)
The article delves into the profound impact of the COVID-19 pandemic on society, education and literature, with a specific focus on the experiences and initiatives of the Literature Department at Shoolini University in Himachal Pradesh, India. It explores the paradoxical nature of the pandemic as both a malevolent force and a catalyst for change. The article discusses the challenges posed by the pandemic, including fear-induced psychosis, domestic conflicts and economic hardships, while also highlighting the importance of adaptability in the face of unprecedented adversity. As a case study, the article describes how Shoolini University’s Literature Department responded to the crisis by organising a series of online literary gatherings, symposia and conferences, fostering connections and providing solace to individuals grappling with the isolation of lockdowns. They also detail the publication of an anthology titled Covid’s Metamorphosis: Stories of our Corona Times, which captures the diverse experiences of individuals during the pandemic. Furthermore, the article explores the shifting landscape of education and pedagogy, emphasising the need for innovative approaches in the post-COVID era. It discusses the integration of practices like yoga and meditation into the curriculum to support holistic well-being and psychological resilience, reflects on the transformative nature of the pandemic, likening it to a tsunami of change and underscores the importance of adaptability, compassion and holistic education in navigating the challenges of the post-pandemic world.